Semantic Correspondence Between Trance-Channeled ET Messages and Ufological Records - Wahbeh, Helané; Glick, Beth; Brinsmead, Erik; Taddeo, Sitara; Wood, Ryan S. (Journal of Scientific Exploration, 2026)
This study examined thematic correspondence between two independently sourced corpora: trance-channeled communications attributed to extraterrestrial intelligences (ETIs) and a large-scale archival ufological dataset (UFODex). A curated sample of 52 channeled submissions was collected and processed into a structured dataset, while UFODex, an evolving corpus of books, periodicals, and archival documents, served as a comprehensive map of UFO-related material. Ten matched questions covering topics such as disclosure, communication, time perception, and technology were posed to both datasets. Semantic similarity was quantified using three transformer-based language models (MiniLM, MPNet, and QA MPNet), allowing for a model-agnostic comparison of conceptual overlap. Average similarity scores ranged from 0.66 to 0.88 across questions, with disclosure, psychic abilities, and time perception showing the highest alignment. Qualitative synthesis revealed convergent themes across both sources, including phased disclosure processes, latent human psi capacities, and nonlinear conceptions of time, while highlighting epistemic divergence. Channeled content emphasized vibrational readiness, ethical co-creation, and consciousness-based contact models, whereas UFODex emphasized secrecy, technological engineering, and geopolitical framing. These findings highlight the value of semantic analysis for mapping conceptual structures across heterogeneous sources and lay the groundwork for future, more controlled comparisons across channeling modalities and related cultural domains.